The Influence of Packaging Elements on Buying Behaviour for Convenience Goods amongst Customers - Faith Tinonetsana; Darry Penceliah (Journal of Economics and Behavioral Studies, 2017)
The role of packaging has changed with the move to self-service retail formats. Marketers have transformed packaging to become one of the major promoting tools to products. There was a necessity to explore packaging and its elements in order to understand which of these elements influence international university students purchase decisions. Thus, this paper seeks to determine the relationship between international university students’ buying behaviour and package elements through linear regression analysis. A quantitative, non-probability research approach was employed. A convenience sample was used to select study 400international students from two South African universities. Research findings reveal that international students’ perception of packaging elements influence their buying behaviour. The results also show that there is a significant relationship between consumer perception and students buying behaviour. Findings also reveal that there is a significant relationship between consumer buying behaviour and seven predictor variables; colour, graphics, packaging technology, label information, brand name, time pressure and level of involvement. It is thus imperative for the marketers to understand that packaging elements have various influences on the consumer depending on context and on product. If the package elements are properly combined, the package will be more attractive and attention grabbing.